Paracoccidioidomycosis in people living with HIV/AIDS: A historical retrospective cohort study in a national reference center for infectious diseases, Rio de Janeiro, Brazil. - Eduardo Mastrangelo Falcão; Priscila Marques de Macedo; Dayvison Francis Saraiva Freitas; Andréa d'Avila Freitas; Beatriz Grinsztejn; Valdiléa Gonçalves Veloso; Rodrigo Almeida-Paes; Antonio Carlos Francesconi do Valle (Public Library of Science (PLoS), 2022)
Paracoccidioidomycosis (PCM) is one of the main endemic systemic mycoses in Latin America, usually occurring in rural areas. When PCM occurs simultaneously with underlying immunosuppressive conditions, it can present as an opportunistic disease. Between 2000 and 2017, literature reported around 200 PCM cases in people living with HIV/AIDS (PLWHA). To address research gaps on this co-infection and to study its possible temporal changes in the last decade, we performed an active co-infection case search on the HIV/AIDS and PCM cohorts from a Brazilian reference center database from 1989 to 2019. We found 20 PLWHA among 684 PCM patients (2.92%), predominantly male (70.0%) and urban workers (80.0%). The median age of patients was higher in the 2010-2019 decade (p = 0.006). The occurrence of PCM in PLWHA was lower when compared with other fungal diseases. Although 50.0% of the patients had already been diagnosed with HIV infection and presented CD4+ T cell counts greater than 200/mm3 at the time of PCM diagnosis, the suspicion of immunosuppression in the context of atypical and more severe clinical forms of PCM revealed the diagnosis of HIV infection in 35.0% of the patients. Two (10.0%) patients had an evolution compatible with immune reconstitution inflammatory syndrome (IRIS) after starting antiretroviral therapy (ART).We highlight the importance of considering a PCM diagnosis in PLWHA to prevent a late-onset treatment and progression to severe manifestations and unfavorable outcomes. In addition, HIV investigation is recommended in PCM patients, especially those with atypical and more severe clinical presentations.